Tectonic Setting of the Kenya Rift in the Nakuru Area, Based on Geophysical Prospecting - Paolo Conti; Marco Pistis; Stefano Bernardinetti; Alessio Barbagli; Andrea Zirulia; Lisa Serri; Tommaso Colonna; Enrico Guastaldi; Giorgio Ghiglieri (Geosciences, 2021)
In this paper, we present results of tectonic and geophysical investigations in the Kenya Rift valley, in the Nakuru area. We compiled a detailed geological map of the area based on published earlier works, well data and satellite imagery. The map was then integrated with original fieldwork and cross sections were constructed. In key areas, we then performed geophysical survey using Electrical Resistivity Tomography (ERT), Hybrid Source Audio MagnetoTelluric (HSAMT), and single station passive seismic measurements (HVSR). In the study area, a volcano-sedimentary succession of the Neogene-Quaternary age characterized by basalts, trachytes, pyroclastic rocks, and tephra with intercalated lacustrine and fluvial deposits crops out. Faulting linked with rift development is evident and occurs throughout the area crosscutting all rock units. We show a rotation of the extension in this portion of the Kenya rift with the NE–SW extension direction of a Neogene-Middle Pleistocene age, followed by the E–W extension direction of an Upper Pleistocene-Present age. Geophysical investigations allowed to outline main lithostratigraphic units and tectonic features at depth and were also useful to infer main cataclasites and fractured rock bodies, the primary paths for water flow in rocks. These investigations are integrated in a larger EU H2020 Programme aimed to produce a geological and hydrogeological model of the area to develop a sustainable water management system.